Digital disconnect how capitalism is turning the Internet against democracy - McChesney, Robert Waterman (New York The New Press, 2013)
McChesney?s award-winning Rich Media, Poor Democracy skewered the assumption that a society drenched in commercial information is a democratic one. In Digital Disconnect, McChesney returns to this provocative thesis in light of the advances of the digital age. He argues that the sharp decline in the enforcement of antitrust violations, the increase in patents on digital technology and proprietary systems and massive indirect subsidies and other policies have made the internet a place of numbing commercialism. A handful of monopolies now dominate the political economy, from Google, which garners a 97 percent share of the mobile search market, to Microsoft, whose operating system is used by over 90 percent of the world?s computers. Capitalism?s colonization of the Internet has spurred the collapse of credible journalism and made the Internet an unparalleled apparatus for government and corporate surveillance and a disturbingly antidemocratic force.
Includes bibliographical references (pages 233-284) and index.
Keywords: Internet--Political aspects